2015
DOI: 10.1186/s40645-015-0049-2
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall intensity–duration conditions for mass movements in Taiwan

Abstract: Mass movements caused by rainfall events in Taiwan are analyzed during a 7-year period from 2006 to 2012. Data from the Taiwan Soil and Water Conservation Bureau reports were compiled for 263 mass movement events, including 156 landslides, 91 debris flows, and 16 events with both landslides and debris flows. Rainfall totals for each site location were obtained from interpolated rain gauge data. The rainfall intensity-duration (I-D) relationship was examined to establish a rainfall threshold for mass movements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 61 publications
(101 reference statements)
0
47
1
3
Order By: Relevance
“…Em seu trabalho, Caine (1980) propôs uma relação limiar global entre intensidade e duração de precipitação capaz de desencadear escorregamentos utilizando 73 eventos de escorregamentos e fluxo de detritos. Apesar de a abordagem empírica negligenciar importantes aspectos hidrológicos atuantes no solo, fornece um meio simples de emissão de alertas a movimentos de massa baseado apenas em precipitação (CHEN et al, 2015).…”
Section: Introdução E Objetivounclassified
“…Em seu trabalho, Caine (1980) propôs uma relação limiar global entre intensidade e duração de precipitação capaz de desencadear escorregamentos utilizando 73 eventos de escorregamentos e fluxo de detritos. Apesar de a abordagem empírica negligenciar importantes aspectos hidrológicos atuantes no solo, fornece um meio simples de emissão de alertas a movimentos de massa baseado apenas em precipitação (CHEN et al, 2015).…”
Section: Introdução E Objetivounclassified
“…The I-D threshold for mass movements is identified on an I-D plot as the minimum rainfall for which a landslide could occur (Chen, 2015). Average rainfall intensity, duration, and cumulative rainfall for debris flow/mud flow were 49 mm/h, 7 h, and 260 mm respectively, and those for landslides were 41 mm/h, 5 h, and 210 mm respectively (Table 1).…”
Section: Rainfall Intensity-duration (I-d) Thresholdmentioning
confidence: 99%
“…International literature revealed that various methods have been used to establish the relationship between rainfall intensity and duration [12] [37], however the general form of the relationship between rainfall intensity and duration…”
Section: Threshold Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the assistance of seismic records, the time information for estimating critical rainfall can be acquired. 25 By applying various rainfall factors into statistical analysis, a statistical threshold can be built to explore the critical rainfall conditions of landslide occurrences, such as using rainfall intensity and duration to define rainfall threshold curves (Caine, 1980;Guzzetti et al, 2008;Saito et al, 2010;Chen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%